2014
DOI: 10.1007/s11745-014-3913-8
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol Increases Liver and Serum Docosahexaenoic Acid in Mice Fed Varying Levels of α‐Linolenic Acid

Abstract: Docosahexaenoic acid (DHA) is considered to be important for cardiac and brain function, and 17β-estradiol (E2) appears to increase the conversion of α-linolenic acid (ALA) into DHA. However, the effect of varying ALA intake on the positive effect of E2 on DHA synthesis is not known. Therefore, the objective of this study was to investigate the effects of E2 supplementation on tissue and serum fatty acids in mice fed a low-ALA corn oil-based diet (CO, providing 0.6 % fatty acids as ALA) or a high ALA flaxseed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Many assume that ALA has less potent effects than its longer chain EPA and DHA metabolites (49), but our study shows that ALA at lower doses (50 mM) significantly reduces the growth not only of MCF-7 and MDA-MB-231 cell lines, but also the HER2 overexpressing BT-474 and TNBC MDA-MB-468 cell lines, both with and without E2. As previously indicated, the 50 mM ALA that caused growth reduction of BC cells is physiologically relevant, with serum ALA concentrations in animal and clinical studies exceeding this with intakes of 4% flaxseed oil and 6 g/day ALA diets, respectively (34)(35)(36)(37). A comparison of the cell lines showed that MDA-MB-231 cells have significantly larger reductions in growth from ALA treatment (75 mM) compared to the luminal A MCF-7 cells.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Many assume that ALA has less potent effects than its longer chain EPA and DHA metabolites (49), but our study shows that ALA at lower doses (50 mM) significantly reduces the growth not only of MCF-7 and MDA-MB-231 cell lines, but also the HER2 overexpressing BT-474 and TNBC MDA-MB-468 cell lines, both with and without E2. As previously indicated, the 50 mM ALA that caused growth reduction of BC cells is physiologically relevant, with serum ALA concentrations in animal and clinical studies exceeding this with intakes of 4% flaxseed oil and 6 g/day ALA diets, respectively (34)(35)(36)(37). A comparison of the cell lines showed that MDA-MB-231 cells have significantly larger reductions in growth from ALA treatment (75 mM) compared to the luminal A MCF-7 cells.…”
Section: Discussionmentioning
confidence: 72%
“…Medium was switched to treatment medium with 0, 50, 75, 100, 125, 150, or 200 mM ALA § 1 nM E2, 3 wells per treatment condition. These concentrations were selected because they are physiological, based on in vivo mouse and rabbit plasma concentrations achieved after ALA supplementation ranging from 98 to 600 mM (34,35), and human plasma ALA concentrations over 200 mM with diet supplementation of 6 g ALA/day (36,37). The above levels have also been used in many previous in vitro research (5)(6)(7)(8)(38)(39)(40)(41)(42).…”
Section: Cell Growth/viabilitymentioning
confidence: 99%
“…Control medium contained no ALA but with the same concentration of FBS and E2. A concentration of 75 μM ALA was selected as it reduces growth by at least 50% in these four BC cell lines after 96 h treatment time [49], and is physiologically relevant as in vivo studies in mice showed serum concentrations over 100 μM after feeding a 10% FS or 4% flaxseed oil diet [15,28] and human serum reached 197.5 μM with intake of a 6 g/day ALA diet [2]. Treatment medium contained E2 to ensure usual growth in estrogen dependent cell lines.…”
Section: Fatty Acid Treatmentmentioning
confidence: 99%
“…Serum and tumor levels of ALA and long chain n-3 PUFAs EPA and DHA are significantly higher in mice fed 4 % FSO or 10 % FS diets compared to corn oil-based basal diets [ 7 , 11 , 12 , 14 ]. DHA and DHA-rich fish oil have demonstrated anticancer effects [ 15 20 ] and have also been shown to affect HER2 signaling [ 17 ] in models of HER2 overexpressing breast cancer.…”
Section: Introductionmentioning
confidence: 99%